Humanitarian Intervention: Institutional Support from the Ministry of Law and Human Rights of the Republic of Indonesia - Yuditia Nurimaniar; Hilmi Ardani Nasution (Badan Strategi Kebijakan Hukum, 2022)
Humanitarian intervention is an act of intervention using armed forces for humanitarian purposes. Indonesia as a country that has a role to participate in maintaining world security and order has the potential to carry out humanitarian interventions. The implementation of humanitarian intervention requires in-depth consideration and study. Therefore, this study tries to find out about the aspect of law and human rights institutions in the implementation of humanitarian intervention conducted by Indonesia. The method used is normative research, by reviewing existing regulations that are related to humanitarian intervention. The Ministry of Law and Human Rights based on its structure and function has a major role in the implementation of humanitarian interventions, both in the initial phase of initiation until the initiation of the intervention is approved for implementation. The role of the Ministry of Law and Human Rights needs to be encouraged to be fully involved in the implementation